Respostas

A melhor resposta!
2014-07-03T16:12:13-03:00
Como o elevado á menos é transformado em fração temos.
a) 2^{-3}= \frac{1}{ 2^{3} }= \frac{1}{2.2.2}= \frac{1}{8}
c)(-3).(-3)=9
d)-(3).(3)=-9
e) \sqrt{196} = \sqrt{14.14}= \sqrt{ 14^{2} } =14
f)3+16=19
g) (x+1)^{2}=(x+1)(x+1)= x^{2} +2x+1
h)(2x+3)^{2}=(2x+3)(2x+3)=4 x^{2} +12x+9
i)(X+3)(X-3)= x^{2} -9
J)(X+1)(X-3)= x^{2} -2x-3
h)2 \sqrt{4}.3 \sqrt{2} =2.3. \sqrt{4.2}=6. \sqrt{8}=6 \sqrt{2.2.2}=6 \sqrt{ 2^{2}.2 }=6.2 \sqrt{2}=12 \sqrt{2}
i)3\sqrt{3} -2 \sqrt{3}=(2-3) \sqrt{3}=-1 \sqrt{3}=- \sqrt{3}
1 5 1